Prevalence of Campylobacter Species in Out-Patients and Pregnant Women Attending Government Clinics in Sokoto State, Nigeria - Innocent Okwundu Nwankwo; Olufemi Oludayor Faleke; Mohammed Danlami Salihu; Abdullahi Alhaji Magaji (Journal of Preventive Medicine And Care, 2016)
Campylobacter infection has been detected in poultry processors at live bird markets in Sokoto, however the prevalence of Campylobacter species in more diverse group of the population is uncertain. For this purpose, 292 human fecal swabs from patients in four Government Hospitals in Sokoto State were analyzed for Campylobacter species using culture and phenotypic typing method. The prevalence rate of 55% was revealed in the tested samples while 56% and 55% were for males and females respectively. Campylobacter jejuni, C. coli and C. lari had 20%, 40% and 40% in males and 38%, 35% and 27% in females respectively. The prevalence rates of 60%, 52%, 45%, 41% and 80%,were revealed in age range of (less than 1-6, 7-13, 14-20, 21-55 and 56-76) yrs respectively. Furthermore, 70% and 43% prevalence rates were recorded in pregnant and non-pregnant women of reproductive age respectively. There was no statistical significant association (P>0.05) between Campylobacter infection and age range and sex, but the statistical association between infection and pregnancy was significant (P<0.05). The prevalence of Campylobacter species in patients as found in the various hospitals has revealed the level of environmental contamination in different homes in the state and the need to include Campylobacter in screening routine laboratory diagnosis of gastroenteritis in humans for appropriate treatment and management especially in young children, old adult and pregnant women.
Keywords: Campylobacter species